Pharmacokinetics of amodiaquine and desethylamodiaquine in pregnant and postpartum women with Plasmodium vivax malaria. - Rijken, M; Mcgready, R; Jullien, V; Tarning, J; Lindegardh, N; Phyo, A; Win, A; Hsi, P; Cammas, M; Singhasivanon, P; White, N; Nosten, F (2011)
In order to study the pharmacokinetic properties of amodiaquine and desethylamodiaquine during pregnancy, 24 pregnant women in the second and third trimesters of pregnancy and with Plasmodium vivax malaria were treated with amodiaquine (10 mg/kg of body weight/day) for 3 days. The same women were studied again at 3 months postpartum. Plasma was analyzed for amodiaquine and desethylamodiaquine by use of a liquid chromatography-tandem mass spectrometry method. Individual concentration-time data were evaluated using noncompartmental analysis. There were no clinically relevant differences in the pharmacokinetics of amodiaquine and desethylamodiaquine between pregnant (n = 24) and postpartum (n = 18) women. The results suggest that the current amodiaquine dosing regimen is adequate for the treatment of P. vivax infections during pregnancy.